If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5)=5-3H
We move all terms to the left:
(5)-(5-3H)=0
We add all the numbers together, and all the variables
-(-3H+5)+5=0
We get rid of parentheses
3H-5+5=0
We add all the numbers together, and all the variables
3H=0
H=0/3
H=0
| -1−f=2f−4 | | t-25=227 | | 57=17-3x | | 3x-7=x+8-7 | | -6x=3x-6 | | 7m-8=9m | | x+0.8=27 | | 13-7f=2f-50 | | (t-6)8/5=-0.4 | | -100=2x+40 | | -9u+6=-10 | | 12x-129=6x+75 | | 32=x/9+24 | | 2+3a=23 | | 3z-10=2z-7 | | 6|5p+4|-6=20 | | 3n-15=7n | | |-2-6|=x | | 11x+7-3=10x—4 | | 3x+5x-6=26 | | -4.8(3x-4.18)=58.56 | | 5x-16=-x+7 | | -4(w-1)=4w-28 | | 12x+13+16x-7=180 | | 4x+x+6x-2=180 | | 12+y+4y-2y=36 | | -7y+19=-2(y+8) | | 0=3x^2+21x | | 6(2g+2)-5g=3(4g-5)-3 | | 22x-3=135 | | 4(w-1)=8w+28 | | |B+3|=|2j+3| |